PENGARUH UREA DAN AZOLLA SEBAGAI TANAMAN PENUTUP PADA BUDIDAYA PADI SAWAH TANAH BERKAPUR DI SEKITAR KUPANG, TIMOR, NTT - Tamad Tamad (Research Center for Biology-Indonesian Institute of Sciences, 2002)
The ammonia volatilization from lime soil is a very important factor of N-urea losses. Ammonia volatilization from lime soil is very high due to high buffering capacity and basalt pH of the soil. However, urea is commonly used by farmeru as N-source fertilizer on paddy field. One alternitive is Azolla as cover crop can be used to reduce ammonia volatilization from urea. Azolla as cover crop significantly reduced the pH of flodded water, increased tillers and yield up to 66%. Highest tillers production and yield occurred in the treatment of 250 kgs/ha urea, with yield 5.73 tons/ha of paddy seeds.